Combined EGFR and VEGFR versus single EGFR signaling pathways inhibition therapy for NSCLC: a systematic review and meta-analysis. - Xinji Zhang; Yesheng Li; Hui Li; Yingyi Qin; Chong Bai; Feng Xu; Tianyi Zhu; Jinfang Xu; Mengjie Wu; Chaoxiang Wang; Lixin Wei; Jia He (PLoS ONE)
Background Lung cancer is a heterogeneous disease with multiple signaling pathways influencing tumor cell survival and proliferation, and it is likely that blocking only one of these pathways allows others to act as salvage or escape mechanisms for cancer cells. Whether combined inhibition therapy has greater anti-tumor activity than single inhibition therapy is a matter of debate. Hence, a meta-analysis comparing therapy inhibiting both VEGFR and EGFR signaling pathways with that inhibiting EGFR signaling pathway alone was performed. Methodology and principal findings We searched PubMed, EMBASE database and the proceedings of major conferences for relevant clinical trials. Outcomes analyzed were objective tumor response rate (ORR), progression-free survival (PFS), overall survival (OS) and toxicity. Besides, subgroup analyses were performed to investigate whether the combined inhibition therapy is best performed using combination of selective agents or a single agent with multiple targets. Six trials recruiting 3,302 patients were included in the analysis. Combined inhibition therapy was associated with a 3% improvement in OS as compared with single-targeted therapy, but this difference was not statistically significant (HR, 0.97; 95% CI, 0.89-1.05; P=0.472). Patients receiving combined inhibition therapy had significant longer PFS than the group with single-targeted therapy (HR, 0.80; 95% CI, 0.67-0.95; P=0.011). There was no difference in the ORR between the groups (OR, 1.44; 95% CI, 0.95-2.18; P=0.085). Subgroup analysis revealed that combined inhibition therapy using combination regimens was associated with statistically significant improvement in both ORR and PFS. Toxicity was greater in combined inhibition therapy. Conclusions There is no evidence to support the use of combined inhibition therapy in unselected patients with advanced NSCLC. However, given the significant advantage in ORR and PFS, combined inhibition therapy using combination regimens may be considered for further evaluation in subsets of patients who may benefit from this treatment.